Abrasive Testing of the Gearbox Lubricating Oil Based on Electromagnetic Induction - Wang Liangjian; Chen Qi; Zhang Daocheng; Xia Tongliang; Song Hui; Huang Liyuan (Jixie chuandong)
In order to explore the negative influence rule of the iron debris abrasive particles in the gearbox on the original lubrication system, based on the principle of electromagnetic induction and STM32F103ZET6 microcontroller as the control unit, a set of gearbox lubricating oil abrasive particles online detection system is designed, and the abrasive particle volume and quantity measurement results of the sample oil and a gearbox oil are compared. With the volume of a single abrasive particle as the index, the cleaning degree of lubricating oil in a gearbox is determined, and the influence of gear running at different speeds on the online measurement results are analyzed. The test results show that the gearbox lubricating oil online detection system has good detection effect. The static detection value of the gearbox is much lower than that of the dynamic detection value. When the input gear of the gearbox dynamic detection is larger than a certain speed threshold, the detection results of the abrasive volume and quantity increase obviously. This research has certain practical value for fault diagnosis and risk warning of the gear lubrication system.